Enhanced CO2 separation in membranes with anion-cation dual pathways. Issue 38 (May 2020) - Yan, Zhikun; Zhang, Mengyao; Shi, Feng; Zhu, Bin; Liu, Min; Wang, Shaofei; Li, Yifan; Nunes, Suzana P.
Graphical abstract: Highlights: GO-supported imidazolium polymer brushes are introduced into SPEEK membranes. The composite membranes show ion exchange capacities for both cations and anions. The anion–cation dual pathways are evidenced by proton and bicarbonate transfer data. The "carrier saturation effect" of facilitated transport membranes was not observed. Abstract: The factors contributing to the water-facilitated CO2 capture in membranes are investigated. Since CO2 transports through such hydrated membrane mainly in the form of bicarbonate, there is a pressing need for exploring the ionic transport mechanism. Herein, a series of composite charged membranes comprising a negatively charged polymer matrix and positively charged filler is proposed. For that, polymer brushes bearing imidazolium cations are grafted on graphene oxide and then dispersed in sulfonated poly (ether ether ketone) (SPEEK). Compared with the pristine SPEEK membranes, a significant enhancement in both CO2 permeability and CO2 /N2 selectivity is observed. The encouraging results are discussed considering proton conductivity and bicarbonate diffusivity. More interestingly, the membranes show simultaneously higher CO2 permeability and CO2 /N2 selectivity when the operating pressure or temperature are increased, supporting the occurrence of ionic transport mechanism arising from the unique anion-cation dual pathways at the polymer-filler interface.